2022
DOI: 10.2147/dmso.s386093
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Parameters and Their Correlation with Glycemic Control Among Type 2 Diabetic Adult Patients in Eastern Ethiopia: A Comparative Cross-Sectional Study

Abstract: Background: Diabetes has been proposed to inflict an insult on the hematopoietic milieu marked by changes in hematological indices including red blood cell parameters. Thus, this study aimed to assess the red blood cell parameters and their correlation with glycemic control in type 2 diabetic adult patients in comparison with apparently healthy individuals. Methods: A comparative cross-sectional study was conducted at the chronic illness clinic of Hiwot Fana Comprehensive Specialized University Hospital from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Despite the differences in group means being statistically significant, there may be considerable overlap between individual results in the disease and control groups, impacting the meaningfulness of test results. This is particularly noteworthy for the studies of Arkew et al and Jabeen et al, 1 , 5 , 7 where the differences in group means are ~1 fL, despite the statistically significant difference between the two cohorts. Without a rigorous control of the preanalytical and analytical phase variables, individual patient results may be difficult or impossible to interpret.…”
Section: Dear Editormentioning
confidence: 87%
See 3 more Smart Citations
“…Despite the differences in group means being statistically significant, there may be considerable overlap between individual results in the disease and control groups, impacting the meaningfulness of test results. This is particularly noteworthy for the studies of Arkew et al and Jabeen et al, 1 , 5 , 7 where the differences in group means are ~1 fL, despite the statistically significant difference between the two cohorts. Without a rigorous control of the preanalytical and analytical phase variables, individual patient results may be difficult or impossible to interpret.…”
Section: Dear Editormentioning
confidence: 87%
“…Arkew et al have published an article entitled “Red Blood Cell Parameters and Their Correlation with Glycemic Control Among Type 2 Diabetic Adult Patients in Eastern Ethiopia: A Comparative Cross-Sectional Study” in Diabetes, Metabolic Syndrome and Obesity. 1 I congratulate the authors on their work, which adds to the already extensive literature on the use of the red blood cell distribution width (RDW) as a surrogate biomarker of systemic inflammation in the setting of type 2 diabetes mellitus (T2DM). I would like to add some technical details about the RDW which would be of interest to the readership of the journal who are considering the use of the RDW for this or related purposes.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that hyperglycemia reduced erythrocyte deformability and shortened lifespan, which seemed to cause changes in RDW levels. 27 , 28 However, there are no studies on the relationship between RDW levels and FBG in patients with ACS. Therefore, we investigated the relationship between RDW and FBG or HbA1c in ACS patients but not find a correlation between RDW and HbA1c.…”
Section: Discussionmentioning
confidence: 99%